Sociodemographic clinical aspects and quality of life in patients with rheumatoid arthritis - Ana Paula Shiratori; Rodrigo da Rosa Iop; Franciele Cascaes da Silva; Susana Cristina Domenech; Noé Gomes Borges Júnior; Monique da Silva Gevaerd (Universidade de Fortaleza, 2014)
Objective: To characterize the sociodemographic clinical aspects and quality of life of patients with rheumatoid arthritis (RA). Methods: This was a descriptive, cross-sectional quantitative research that evaluated 22 individuals with RA over 18 years old, regardless of sex. Participants were referred to the Mulstisectoral Analysis Laboratory of the State University of Santa Catarina by rheumatologists of the Brazilian National Health System in the period from June to September 2010. It was used a form to obtain sociodemographic and clinical data, the level of disease activity (Disease Activity Score 28) and the Quality of Life Questionnaire (36 Item Short-Form Health Survey). Results: There was a prevalence of female gender, with 81.8% (n=18); white ethnicity, with 90.9% (n=20); and sixth decade of life, with 60 (±12.9) years for male gender. Among the symptoms, 17 individuals (77.3%) reported pain as the main complaint. Regarding the level of disease activity, the mean values were 4.47±1.56 with a prevalence of 10 patients (45.5%) presenting moderate activity. Concerning QoL, it was found a significant difference in the domains pain / social aspect and the level of disease activity (p <0.05). Regarding the domain pain, there was a significant difference when comparing the groups high and low disease activity (p<0.01) and between the low and moderate groups (p <0.01). Conclusion: It was possible to identify in the individuals with RA participating in this study a deficit in their general state of health. Additionally, the high level of disease activity interfered with painful symptomatology and hindered social aspects. doi:10.5020/18061230.2014.p5